Latvia - Sharing the High Growth Dividend : A Living Standards Assessment - World Bank (Washington, DC, 2012)
Between 1998 and 2004, Latvia achieved substantial progress in poverty reduction, with an estimated 325,000 people moving out of poverty over this period. This report examines the extent and causes of poverty reduction during this period using data from a variety of sources, the national accounts, as well as household budget, labor force, and other household surveys. The report is divided into four sections; Chapter 1 summarizes recent economic developments. It reviews key changes in the Latvian economy over the past decade. It addresses growth trends at the sector level, summarizes changes in income and consumption, and identifies key labor market developments experienced by Latvia in recent years. Chapter 2 examines trends in poverty and inequality, and provides a poverty profile. It uses data from the household budget survey series to shed light on recent trends, and strives to resolve the apparent puzzle of why Laeken poverty indicators show no decline in poverty. The chapter also summarizes the main correlates of poverty, and elaborates on what explains differences in welfare status among different groups. Chapter 3 analyzes the main determinants of employment and earnings. It draws upon data from the labor force survey series, as well as from a recent representative survey of employees conducted in 2005 to examine the links between language skills and earnings. Finally, chapter 4 examines targeting effectiveness of various social assistance programs using data from the 2004 HBS. In particular, the analysis focuses on the coverage, adequacy, and targeting efficiency of the various transfer programs in operation (pensions, state social security benefits, local government assistance benefits, and state social benefits).